2017
DOI: 10.1002/bit.26333
|View full text |Cite
|
Sign up to set email alerts
|

Short DNA containing χ sites enhances DNA stability and gene expression in E. coli cell‐free transcription–translation systems

Abstract: E. coli cell-free transcription-translation (TXTL) systems offer versatile platforms for advanced biomanufacturing and for prototyping synthetic biological parts and devices. Production and testing could be accelerated with the use of linear DNA, which can be rapidly and cheaply synthesized. However, linear DNA is efficiently degraded in TXTL preparations from Escherichia coli. Here, we show that double-stranded DNA encoding χ sites–eight base-pair sequences preferentially bound by the RecBCD recombination mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 20 publications
2
91
0
Order By: Relevance
“…The reactions were carried out as described inWatters, et al (19). Briefly, each reaction was mixed from 9 μL of TXTL master mix, 0.125 nM of each reporter plasmid, 1 nM of Cas9 amplicon or plasmid, 2 nM of sgRNA plasmid, 1 nM of genomic fragment amplicon or Acr candidate plasmid, 1 μM of IPTG, 0.5 μM of anhydrotetracycline, 0.1% arabinose, and 2 μM of annealed oligos containing six χ sites(39).The reactions were run at 29 °C in a TECAN Infinite Pro F200, measuring GFP (λex: 485 nm, λem: 535 nm) fluorescence levels every three minutes for 10 hours. To plot kinetic data, the minimum measured fluorescence intensity was subtracted from each point on the curve (to compensate for early variations due to condensation on the sealing film), then the overall curve was normalized by the fluorescence level measured for the non-targeting negative control after 10 hours of reporter expression.Protein purification.…”
mentioning
confidence: 99%
“…The reactions were carried out as described inWatters, et al (19). Briefly, each reaction was mixed from 9 μL of TXTL master mix, 0.125 nM of each reporter plasmid, 1 nM of Cas9 amplicon or plasmid, 2 nM of sgRNA plasmid, 1 nM of genomic fragment amplicon or Acr candidate plasmid, 1 μM of IPTG, 0.5 μM of anhydrotetracycline, 0.1% arabinose, and 2 μM of annealed oligos containing six χ sites(39).The reactions were run at 29 °C in a TECAN Infinite Pro F200, measuring GFP (λex: 485 nm, λem: 535 nm) fluorescence levels every three minutes for 10 hours. To plot kinetic data, the minimum measured fluorescence intensity was subtracted from each point on the curve (to compensate for early variations due to condensation on the sealing film), then the overall curve was normalized by the fluorescence level measured for the non-targeting negative control after 10 hours of reporter expression.Protein purification.…”
mentioning
confidence: 99%
“…We appended an ssrA degron tag recognized by the ClpXP protease to the C-128 terminus of deGFP ( Figure 2B mitigating potential effects from the end of the dsDNA molecule. We measured the fold-141 repression of the deGFP produced by the reaction after five hours, which is shorter than our 142 previous experiments because linear templates degrade after that time in our TXTL system 143 8 (Marshall et al, 2017). We found that dSpyCas9 was capable of repressing gene expression 144 when targeting the transcribed sequence of the reporter gene on the linear template, but not 145 when targeting the promoter ( Figure 2C).…”
Section: Multiple Factors Impact the Measured Activity Of Dspycas9 Inmentioning
confidence: 83%
“…TXTL reactions were conducted in volumes of 5 µl 507 at 29-30°C. When expressing from linear DNA template, 2 µM of annealed oligos containing six 508 copies of the χ-site sequence (Chi6; for details see (Marshall et al, 2017)) was added to the 509 reaction. 510…”
Section: Materials and Methods 497mentioning
confidence: 99%
“…The program searches for restriction sites used in BioBrick (EcoRI, XbaI, SpeI, PstI, ApoI, MfeI, AvrII, NheI, NsiI, SbfI, NotI), BglBrick (EcoRI, BglII, BamHI, XhoI), MoClo (BsaI, BbsI, MlyI), and GoldenBraid (BsaI, BsmBI, BtgZI) cloning. Additionally, all E. coli chi sites are removed to reduce recombination 20 and enable further engineering 22 . All start codons are unified to ATG and all stop codons are set to TAA.…”
Section: Resultsmentioning
confidence: 99%